ASPECTOS HIDROQUÍMICOS DAS ÁGUAS SUBTERRÂNEAS DA REGIÃO COSTEIRA DE ICAPUI - CEARÁ - Cavalcante, Itabaraci Nazareno; PAIVA, Maria HELENA A; Teixeira, Francisco JOSÉ; BIANCHI, LUIZ (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL